PELAKSANAAN PELAYANAN KESEHATAN RUMAH SAKIT UMUM DAERAH KOTA DUMAI BERDASARKAN UNDANG-UNDANG NOMOR 25 TAHUN 2009 TENTANG PELAYANAN PUBLIK DI MASA PANDEMI VIRUS COVID-19 - Fikri Saputra; Dessy Artina; Muhammad A. Rauf (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2022)
Health is a state of well-being of the body, soul and social life that enables sociallyand economically productive life. The law also regulates health services for its citizens,where Indonesia is currently facing several population health problems that still needserious attention from all parties because the impact will affect the quality of Indonesiain the future. The purpose of writing this thesis, namely; First, to find out theimplementation of health services at the Dumai City Hospital during the Covid-19period based on Law Number 25 of 2009 concerning Public Services, Second, to findout what are the obstacles and conveniences in carrying out Law Number 25 of 2009concerning Public Services in Services the health of the Dumai City Hospital during theCovid-19 period.This type of research is sociological juridical. The data sources used are primarydata and secondary data consisting of primary legal materials, secondary legalmaterials, and tertiary legal materials. Data collection techniques in this study usedobservation, interviews, and literature review. After the data is collected then analyzedto draw conclusions.From the results of the study it was concluded that: First, health services inhandling patients during the Covid-19 pandemic at the Dumai City General Hospitaldid not fully meet service standards according to Law Number 25 of 2009 concerningPublic Services. So it can be concluded that the services provided by the DumaiRegional General Hospital are still not good. Second, obstacles in the implementationof health services in handling patients during the Covid-19 pandemic at the Dumai CityGeneral Hospital, when viewed from indicators of the effectiveness of public serviceshave not been fully maximized, because there are several deficiencies such as: lack ofparking space, lack of rooms and beds for inpatients, lack of medical equipment, lack ofdoctors and nurses, lack of ambulances, lack of human resources in providing servicesin the laboratory department. Author's suggestion, First, Dumai City Regional GeneralHospital is a health center in Dumai City, it is hoped that nurses when providingservices will be more responsive, provide faster services to patients, provide facilitiesthat are still lacking, provide doctors, and provide more services. friendly towardspatients when providing services so that patients feel comfortable and satisfied whenreceiving services to patients. Second, efforts need to be made in order to improvehealth services at the Dumai City General Hospital by increasing the professionalquality of medical personnel, adding vehicle units from ambulances and others,laboratory services need to add medical personnel, and add doctors.Keywords: Health Services-Monitoring-Covid-19 Virus Pandemic